PENGARUH TAGLINE DAN BRAND AMBASSADOR TERHADAP BRAND IMAGE PRODUK NATURE REPUBLIC DI OUTLET TUNJUNGAN PLAZA 6 SURABAYA - Thalia Citra Mellynda; Ety Dwi Susanti (STKIP Persada Khatulistiwa Sintang, 2022)
The industrial sector plays an important role as the main driver and support for the national economy. Strategies to promote products in today's business world to be more creative. The purpose of the study was to determine and simultaneously analyze the influence of Tagline and Brand Ambassador variables on the Brand Image of Nature Republic products. This research used quantitative research methods. In collecting the data, this research uses a questionnaire, the source of the data taken is primary data. Research population of consumers of Nature Republic products at Outlet Tunjungan Plaza 6 Surabaya. To obtain maximum results, the sample taken is 100 respondents to consumers who have purchased Nature Republic products at the Tunjungan Plaza 6 Surabaya Outlet. The sampling technique in this study used non-probability sampling. Classical assumption test consists of Multicollinearity Test, Autocorrelation Test, Normality Test. The analytical technique used in this research is using multiple linear regression analysis. The conclusion of this study is that the Tagline and Brand Ambassador variables simultaneously and partially have a significant effect on Brand image